View HAM to Problem Social in era modern Ummi Fadillah - Ummi Fadillah (International Journal of Students Education, 2024)
Right basic man (HAM) is matter which important for enforced because its existence give guarantee principle equality (equality) for all over people man. Inequality between the fulfillment of human rights and the implementation of obligations Unbalanced human rights are still an interesting discourse in Indonesia. For this reason, this research was carried out with systematic approach literature review with the aim of proposing a human rights legal paradigm based on obligations human rights. From a legal research perspective, the nature of this research is categorized into in study prescriptive. Data in this study sourced from regulationlegislation, books and scientific articles from national and international journals relate with draft human rights and law Ham. Results from this study showthat upholding human rights must see the fulfillment of human obligations, because in generalgeneral somebody can demand right if has fulfil obligation. With By basing rights on obligations, human rights law will be balanced. It is hoped that this article can become a reference in the application of human rights law in Indonesia in effort build justice between rights And obligation basic man.